Modern Trends in the Tax Audit Market - Udovikova, Alla A.; Marchenkova, Irina N. (International Journal of Criminology and Sociology, 2022)
As Russia transited to market relations, it formed an independent audit service, which emergence prerequisites were the mutual interest of state bodies, the managing administration of the enterprise and its owners in reliable financial and accounting information. The audit has become an integral part of economic relations and has been recognized by most countries of the world. This was facilitated by the need for means of implementing and protecting property interests, enhancing economic benefits and minimizing entrepreneurial risk. The main aim of the study is to investigate the market economy and tax audit market, which determine the development of new activities for the implementation and regulation of economic relations, predetermined the creation of organizations that regulate the processes of accounting and tax accounting. To accomplish that aim, the methods of deduction, induction, systematization and generalization of theoretical and practical materials are utilized. Based on the outcomes, a new type of activity at that time was an audit, which provided protection of the legal property interests of business entities by means of independent financial control, confirmation of the authenticity of balance sheets and reports on the results of economic activities, and the provision of related services.